Enhanced dissolution of naproxen from pure-drug, crystalline nanoparticles: A case study formulated into spray-dried granules and compressed tablets - Konnerth, Christoph-Günther; Peukert, Wolfgang; Braig, Veronika; Lee, Geoffrey (International Journal of Pharmaceutics, 2019)
This is a case study of the use of rapidly-dissolving naproxen crystalline nanoparticles to prepare compressed tablets. The dissolution rates of different formulations were determined: the crystalline pure-drug nanodispersion, a pure-drug microsuspension, a granule prepared by spray drying the nanodispersion with mannitol, and a tablet prepared by compressing the granule with a bulking agent and a disintegrant. The goal was to determine the influence of each of the process steps on the rapid dissolution of the nanodispersion. A procedure was developed to allow sampling during the first 120 s of dissolution. Dissolution of the nanodispersion was completed after 60 s under both sink and non-sink conditions. Spray drying with mannitol delayed dissolution slightly under both sink and non-sink conditions. Under sink conditions a microsuspension (volume median size 11 µm) showed similar rapid dissolution to the nanodispersion. We propose this to be a result of rapid shrinkage of the microparticles on dissolution under sink conditions. This nullifies any effects of specific surface on dissolution rate. Under non-sink conditions the microparticles retain their lower specific surface for a longer time during dissolution and dissolve therefore more slowly. When compressed into tablets, the dissolution rates of nanoparticles or microparticles were determined primarily by the tablet disintegration time; the influence of sink or non-sink conditions was only observable after disintegration.
UnivIS-Import:2019-08-15:Pub.2019.nat.dchph.lphte.enhanc
Keywords: Low-soluble drug; Dissolution; Spray-drying; Nanosuspension; Tablet